2014
DOI: 10.1371/journal.pone.0099527
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Adult Generated Hippocampal Neurons Is Altered in Circadian Arrhythmic Mice

Abstract: The subgranular zone of the hippocampal formation gives rise to new neurons that populate the dentate gyrus throughout life. Cells in the hippocampus exhibit rhythmic clock gene expression and the circadian clock is known to regulate the cycle of cell division in other areas of the body. These facts suggest that the circadian clock may regulate adult neurogenesis in the hippocampus as well. In the present study, neurogenesis in the hippocampal subgranular zone was examined in arrhythmic Bmal1 knockout (-KO) mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
4
27
0
Order By: Relevance
“…Adult Bmal1 −/− mice show a higher survival rate of NPCs in the DG as compared to Bmal1 +/+ mice. This is consistent with the previously observed enhanced survival in young adult Bmal1 −/− mice interpreted as impaired pruning of newly generated neurons [ 15 ]. Moreover, adult Bmal1 −/− mice showed a significantly lower number of apoptotic cells with no change in DG volume consistent with the decline in cell death during aging in combination with a stable DG volume from 6 weeks of age onwards [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Adult Bmal1 −/− mice show a higher survival rate of NPCs in the DG as compared to Bmal1 +/+ mice. This is consistent with the previously observed enhanced survival in young adult Bmal1 −/− mice interpreted as impaired pruning of newly generated neurons [ 15 ]. Moreover, adult Bmal1 −/− mice showed a significantly lower number of apoptotic cells with no change in DG volume consistent with the decline in cell death during aging in combination with a stable DG volume from 6 weeks of age onwards [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…Oxidative stress leads to decreased proliferation and neuronal differentiation capacity, and induces cellular senescence in NPCs [ 33 , 49 ]. It also activates compensatory mechanisms to minimize cell death by interference with apoptotic signalling pathways [ 49 ]; which is consistent with enhanced survival of NPCs shown in this study and observed previously in Bmal1 −/− mice [ 15 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, others found no significant difference in the cellular proliferation in Bmal1 knockout mice, yet survival of proliferating cells, was significantly greater in Bmal1 knockout animals (Rakai et al, 2014).…”
Section: Ahnmentioning
confidence: 94%